(untitled) (American Journal of Arts and Human Science, 2023)
This current research exposes and analyzes the general situation of medical English dictionary utilization among contemporary Chinese tertiary medical students. Eighty medical students from a Chinese medical university took part in the research and they were asked to answer purposefully designed questionnaires. A follow-up interview was also conducted to collect further data regarding medical English dictionary utilization. The results of the current research have shown that there is a strong need of medical English dictionary utilization among contemporary Chinese tertiary medical students as well as a severe lack of guidance for medical English utilization from medical teachers in Chinese medical universities. The current research further suggests that medical teachers should also guide medical students to meet the needs of selecting proper medical English dictionaries sensibly to facilitate them to utilize their own medical English dictionaries as possible as they can in their medical English learning practice.